Cis- and trans-perfluorodecalin: Infrared spectra, radiative efficiency and global warming potential. (December 2017) - Le Bris, Karine; DeZeeuw, Jasmine; Godin, Paul J.; Strong, Kimberly
Abstract: Perfluorodecalin (PFD) is a molecule used in various medical applications for its capacity to dissolve gases. This potent greenhouse gas was detected for the first time in the atmosphere in 2005. We present infrared absorption cross-section spectra of a pure vapour of cis - and trans -perfluorodecalin at a resolution of 0.1 cm −1 . Measurements were performed in the 560–3000 cm −1 spectral range using Fourier transform spectroscopy. The spectra have been compared with previous experimental data and theoretical calculations by density functional theory. The new experimental absorption cross-sections have been used to calculate a lifetime-corrected radiative efficiency at 300 K of 0.62 W m −2 ppb −1 and 0.57 W.m −2 .ppb −1 for the cis and trans isomers respectively. This leads to a 100-year time horizon global warming potential of 8030 for cis -PFD and 7440 for trans -PFD. Abstract : Highlights: Experimental mid-infrared cross-sections of cis - and trans -perfluorodecalin. Comparison with previous experimental measurements and density functional theory. Radiative efficiency and global warming potential of the compound.